"Авось выведу величавую, положительную фигуру" (про особливості сакралізації пізньої творчості М. Гоголя і Ф. Достоєвського - Сквіра, Н.М. (Слово і Час, 2019)
У статті на прикладі “Мертвих душ” М. Гоголя та “Братів Карамазових” Ф. Достоєвського
виокремлено стрижневі для письменників ідеї, мотиви, сюжетні збіги. Їх сукупність являє
собою інтертекстуальне полотно, покликане сакралізувати тканину тексту. Прийоми авторської
ретроспекції акцентують увагу читача, актуалізуючи осьові біблійні формули. Слово Святого
Письма виразно пронизує мову творів авторів, не лише формуючи стилістичний вектор розповіді
з притаманним їй латентним дидактизмом, а й указуючи на авторитетність Першоджерела.
“Жестові ситуації” дають змогу письменникам докладніше вималювати психологічний образ
героїв, а також співвіднести їхні душевні порухи з міленарним виміром буття. The paper deals with Gogol’s “Dead Souls” and Dostoyevsky’s “The Brothers Karamazov”. The
author investigates main ideas, motives, plot coincidences, which are core for the works. The word of
the Holy Scripture clearly permeates the language of the works by Gogol and Dostoyevsky, forming
the stylistic direction of the narrative with its inherent didacticism and emphasizing the credibility of
the original Source. The aim of the Bible intertext is to sacralize the whole of the text. The writers’
techniques of retrospection enhance the reader’s attention and actualize pivotal biblical formulas.
The researcher states that some episodes of “The Village of Stepanchikovo and Its Inhabitants”
by Dostoyevsky cover the ideas of “Selected Passages from Correspondence with Friends” by
Gogol, and also extend the content components of the statements articulated by the heroes’ of the
second volume of “Dead Souls”. The chapter of “The Brothers Karamazov” called “Conversations
and Exhortations of Father Zosima” by its style, didactic pathos, plot, motive combinations and the
names of the sub-chapters reminds “Selected Passages from Correspondence with Friends”. Gogol’s
phrase “Love us black, anyone can love us white” repeatedly echoes in the replicas of the characters
of “The Brothers Karamazov” and becomes universalized to the formula: “Love a man even in his sin,
for that is the semblance of Divine Love and is the highest love on earth. Love all God’s creation… If
you love everything, you will perceive the divine mystery in things… And you will come at last to love
the whole world with an all-embracing love”.
The image of Troyka (Carriage-and-Three) makes the image of Russia in the studied works by Gogol
and Dostoevsky more profound, accumulating the core idea of the writers – the revival of society.
‘Gesture situations’ allow the writers to describe a psychological image of the characters in detail
and to relate their spiritual movement with a millenary dimension of existence.